Single-Cell Transcriptomics-Guided Network Pharmacology of Traditional Chinese Medicine in Tumor Microenvironment Regulation - Niceles Wetsan; Ishaan Freeman; Dominik Nearris (International Journal of Clinical and Translational Medicine, 2026)
The tumor microenvironment is now understood as a heterogeneous, dynamically regulated ecosystem whose cellular states, molecular gradients, and spatial architectures jointly determine tumor progression and therapeutic response. Traditional Chinese Medicine formulations offer multi-component interventions that may modulate this ecosystem through coordinated action on multiple targets, yet their mechanistic opacity has limited clinical translation. This paper develops a systems-oriented framework in which single-cell transcriptomics functions as a high-resolution observational layer, while network pharmacology supplies an inferential architecture for mapping herbal constituents to cellular regulatory programs. The integration of these layers enables the identification of cell-type-specific responses, ligand-receptor perturbations, and multicellular network shifts associated with TCM exposure. We examine structural trade-offs among data granularity, computational complexity, model interpretability, and clinical generalizability. The discussion addresses modular architectures for data harmonization, network community detection, signature matching, and machine learning-based prioritization, together with considerations of data provenance, reproducibility, fairness, and regulatory oversight. Rather than proposing a single computational protocol, the paper emphasizes the governance of evidence generation, the sustainability of data infrastructures, and the policy conditions under which single-cell-guided network pharmacology can evolve into a trustworthy translational instrument. The resulting perspective situates TCM research within broader precision oncology and systems medicine agendas, highlighting both the promise and the infrastructural burdens of integrating traditional therapeutics with modern high-resolution molecular science.